Perilaku Generasi Z Di Media TikTok Dalam Pemilihan Umum Presiden 2024 - Ni Wayan Ribayanti; Dian Trianita Lestari (CV. ITTC INDONESIA, 2025)
This study aims to examine Generation Z's behavior in utilizing TikTok as a source of political information during the 2024 Presidential Election in Kendari City. Using a qualitative approach and the uses and gratification theory, the author conducted interviews with 13 Generation Z individuals who are active TikTok users and participated in the election. The findings indicate that TikTok was chosen because it presents political content in an engaging, concise, and digitally relevant format for Gen Z. TikTok functions not only as an entertainment platform but also as an effective space for political discussion and expression. The study also found that Gen Z is not a passive media consumer; rather, they actively engage in discussions, filter information, and shape political opinions. Therefore, enhancing political digital literacy is essential to encourage young voters to become more critical and responsible participants in the democratic process.